STRESS DISTRIBUTION ALONG THE CROSS SECTION OF THE NARROWEST PART OF THE DIAPHRAGM SPRING FINGERS (Balkan Journal of Applied Mathematics and Informatics, 2022)
Torque from the engine of the vehicles to the transmission of the cars  is transferred using friction clutches. Part of these clutches is diaphragm spring. In this paper, using Finite Element Method is studied the distribution of the stress along the cross section of the narrowest part of the diaphragm spring fingers and the intensity of the changes of the stress differences in individual parts of this section.
Keywords: diaphragm spring; friction clutch; stress distribution; diaphragm spring fingers